Model Grow Sebagai Pendekatan Alternatif Dalam Proses Coaching Diklat Kepemimpinan Tingkat IV Di PKP2A II LAN - Nirwaty Yapardi; Milawaty Milawaty (Jurnal Transformasi Administrasi, 2016)
The practice of coaching at Lembaga Administrasi Negara starts when the new pattern of training and education on Leadership Training and Prajabatan Training was implemented. One of the models was GROW developed by John Whitmore. The aim of the the present research was to examine the GROW model as an alternatif approach to the process of coaching in leadership education and training at PKP2A II LAN. Using qualitative data from 33 informants, the current research showed that the GROW model can be used as an alternatif approach to the coaching process in leadership education and training level IV. The practice of the model was mainly seen on goal, reality, and will phase.